2019
DOI: 10.3390/plants8070233
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic and Autotoxic Effects of Medicago sativa—Derived Allelochemicals

Abstract: In this study, the allelopathic properties of Medicago sativa on different weeds were investigated under in vitro conditions. The compounds involved in the autotoxicity of M. sativa were analyzed using high-performance liquid chromatography. The extracts of all concentrations inhibited the growth of the calluses of Digitaria ciliaris, Chenopodium album, Amaranthus lividus, Portulaca oleracea, and Commelina communis. Six allelopathic compounds in alfalfa were identified and quantified, and the most predominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 72 publications
3
42
0
1
Order By: Relevance
“…Previous studies on autotoxicity of forage were mainly focused on alfalfa and less reports of autotoxicity about Gramineae (Ghimire, 2019). The present study clearly demonstrated that drooping wildryegrass had autotoxicity during its germination and seedling growth.…”
Section: Figuresupporting
confidence: 65%
“…Previous studies on autotoxicity of forage were mainly focused on alfalfa and less reports of autotoxicity about Gramineae (Ghimire, 2019). The present study clearly demonstrated that drooping wildryegrass had autotoxicity during its germination and seedling growth.…”
Section: Figuresupporting
confidence: 65%
“…Thus, by inducing changes in the vital processes, an improvement in the quality and quantity of the crops appears, as well as an increase in production [2]. The literature data provides numerous information regarding the influence of polyphenolic compounds in seed germination and plant development, in the form of global crude extracts, fractions or individual compounds obtained from different plant sources [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Alfalfa cultivar AC Blue J may have reduced alfalfa autotoxicity Generally, seeding alfalfa on old alfalfa stands or recently broken alfalfa pasture is not recommended as the new plants suffer from "alfalfa sickness", a term used to describe the autotoxicity effect that old alfalfa plants have on newly developing plants (Ghimire, Ghimire, Yu, & Chung, 2019;Hedge & Miller, 1990;Miller et al, 1988). As per recommendations, producers generally wait for a year or two before reestablishing alfalfa and seed a cereal crop to clean the plots.…”
Section: 2mentioning
confidence: 99%